2013
DOI: 10.18052/www.scipress.com/ilns.6.78
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Biofertilizers on Protein, Moisture and Ash Content in Relation to Swelling Property, Water Absorption Capacity, Mineral Elements, Total Phenolic Level of Stevia (<i>Stevia rebaudiana</i> Bert.) Plant Grown under Acidic Soil Zone of South India

Abstract: The field experiment on Stevia rebaudiana (SR), (Family: Asteraceae) was carried out in acid soil zone of Shimoga (Karnataka) in the year 2009 and 2010 to investigate the influence of biofertilizers on protein, moisture and ash content in the dried Stevia leaf and their correlation with swelling property, water absorption capacity and mineral element contents. Results revealed that second harvested sample (August) in first year (2009) was better for all aspects than other harvested samples and the results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…All individual extracts showed potential antimicrobial activity compared to standard ampicillin, but the activities were lower than standard which was similar to the results found in our study [45].…”
Section: Discussionsupporting
confidence: 91%
“…All individual extracts showed potential antimicrobial activity compared to standard ampicillin, but the activities were lower than standard which was similar to the results found in our study [45].…”
Section: Discussionsupporting
confidence: 91%
“…Many authors gave light upon the various kinds of organic fertilizers (organic manures, green manures, composted residues, town refuse, sludge, biogas and animal wastes) and explained their importance on soil properties (physical, chemical, biological) which increase soil fertility and subsequently increase the growth, yield and improve the quality of crops (Kononova, 1966;Tandon, 1992;El-Galla, 2003 andAbo-Alkhair, 2013). The ash content was higher in third harvested sample with simultaneous increased amount of Fe, Mn, Cu and Zn contents due to the residual effect of bio fertilizers (Das and Dang, 2014).…”
Section: Introductionmentioning
confidence: 92%
“…In stevia, these triple associations improved biometric parameters, uptake of nutrients and water from soil, SVglys content, and protein, mineral, and phenol contents. These latter compounds in turn improved the antioxidant activity of leaf extracts [182]. Zare Hoseini et al [183] observed an increased biomass production and microelements content in plants biofertilized with Piriformaspora indica and Glomus mosseae.…”
Section: Mycorrhizal Association and Plant Growth Promoting Rhizobactmentioning
confidence: 99%